Three-dimensional O(N)-invariant ϕ4 models at criticality for N≥4 - Hasenbusch, Martin (Physical review, 2022)
We study the O(N)-invariant ϕ4 model on the simple cubic lattice by using Monte Carlo simulations. By using a finite-size scaling analysis, we obtain accurate estimates for the critical exponents ν and η for N=4, 5, 6, 8, 10, and 12. We study the model for each N for at least three different values of the parameter λ to control leading corrections to scaling. We compare our results with those obtained by other theoretical methods.
Gesehen am 07.04.2022
Im Titel ist die Zahl 4 nach phi hochgestellt